The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1969
DOI: 10.1177/00220345690480051701
|View full text |Cite
|
Sign up to set email alerts
|

The Function and Reliability of the Orogranulocytic Migratory Rate as a Measure of Oral Health

Abstract: The phenomenon of leukopedesis in gingival and periodontal tissues was measured by counting the number of orogranulocytes migrating into the mouth during repeated intervals of 30 seconds. Measurements were carried out with a computerized electronic cell grading system and classified as a nonsubjective laboratory routine for indexing oral inflammation. For orogranulocytic migratory rate (OMR) readings above 1.2 X 10,/30 sec, a minimum of three determinations is required for reliability. Single readings suffice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

1970
1970
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 3 publications
1
34
0
Order By: Relevance
“…Klinkhammer et al (1968) standardized collection and counting of leukocytes in saliva and developed the orogranulocytic migratory rate (OMR). The OMR was found to be correlated with gingival index (Klinkhammer & Zimmerman 1969). In an experimental gingivitis model, the number of granulocytes in saliva increased before the appearance of clinical gingivitis (Friedman & Klinkhammer 1971, Skougaard et al 1969.…”
Section: Inflammatory Cellsmentioning
confidence: 90%
“…Klinkhammer et al (1968) standardized collection and counting of leukocytes in saliva and developed the orogranulocytic migratory rate (OMR). The OMR was found to be correlated with gingival index (Klinkhammer & Zimmerman 1969). In an experimental gingivitis model, the number of granulocytes in saliva increased before the appearance of clinical gingivitis (Friedman & Klinkhammer 1971, Skougaard et al 1969.…”
Section: Inflammatory Cellsmentioning
confidence: 90%
“…Earlier studies, which utilized time‐consuming serial rinses and counting techniques, found similar correlations (12,18). It has been previously shown that the rate at which oral neutrophils migrate into the oral cavity increases in the presence of inflammation (10) and that oral neutrophil counts positively correlate with both increasing pocket depth and the gingival index (11,12). Interestingly, Raeste & Aura (13) found that the leukocyte count in the first rinse of the OMR series also reflects the severity of periodontal disease.…”
Section: Discussionmentioning
confidence: 99%
“…This histological evidence unequivocally demonstrated an increase in polymorphonuclear leukocyte emigration into the gingiva as the first histological indication of a gingival inflammatory response. As later demonstrated by Klinkhamer and Zimmerman (1969) and later by Golub et al (1981), this response can occur within minutes to hours, rather than the days to weeks it normally takes to identify the clinical signs.…”
Section: Short-chain Carboxylic Acid Generation By Periodontal Microbmentioning
confidence: 95%
“…These results may, in part, explain the apparent association between gingival inflammation and periodontal disease. These results may also, in part, explain the absence of a predictive relationship between gingival inflammation and subsequent periodontal disease progression (Lang et al, 1990 A re-assessment of these subjective measures began slowly with the observation that oral leukocyte numbers increase concurrently with gingival inflammation (Klinkhamer and Zimmerman, 1969). The pioneering histological characterization and classification of the gingival inflammatory response solidified this hypothesis (Page and Schroeder, 1976).…”
Section: Short-chain Carboxylic Acid Generation By Periodontal Microbmentioning
confidence: 99%
See 1 more Smart Citation